Physical properties and in vitro studies of sustained-release ketoprofen matrix tablets - Ibrahim Ijang; Mohd Cairul Iqbal Mohd Amin; Bukhori Abu Bakar (Universiti Kebangsaan Malaysia, 2010)
The use of sustained release tablet formulation for non-steroidal anti-inflammatory drugs (NSAIDs) like aspirin has shown its capability to protect the stomach lining from the adverse effect of gastric juice from the body. This study was carried out to evaluate the efficiency of sustained release matrix tablet formulation using ketoprofen as a model drug with different polymers concentration. The tablets were prepared by the wet granulation method using hydrophilic polymer (hydroxypropyl methylcellulose), hydrophobic pH dependent polymer (Eudragit L100-55) and independent polymer (Eudragit RD 100) as matrix forming retarding materials at 10%w/w, 20%w/w and 30%w/w. All formulations were compressed using 10 mm concave faced punches. The compressed tablets were evaluated for uniformity of weight, friability, hardness, thickness, % drug content and in vitro dissolution test with regard to BP 2007. The results showed that the drug release rate was found to be governed by the type and concentration of polymer in the matrix system. Generally, increasing the polymeric concentration in the matrix tablets will decrease the rate of drug release. When the polymers were compared at similar concentration using t50%, the difference in drug release was found to be statistically significant (p<0.05). Based on the in vitro drug dissolution studies, the hydrophobic pH dependent polymer (Eudragit L100-55) showed a better zero drug release profile compared to other polymers.